Economic Analysis of DEWA's Strategic Positioning and Financial Performance in The GCC Energy Sector: A Cost-Benefit Assessment of ‎Strategic Opportunities (2010-2024)‎ - Iyer, Dr Shankar Subramanian; Mehrotra, Dr. Arpita; Raji, Dr Brinitha; Faculty, Dr. Rajesh Arora; Subramanian, Dr Raman (International Journal of Accounting and Economics Studies, 2025)
This study provides a comprehensive economic and financial analysis of Dubai Electricity and ‎Water Authority's (DEWA) strategic positioning within the Gulf Cooperation Council (GCC) ‎energy sector from 2010-2024. Using quantitative financial analysis and performance ‎benchmarking methodologies, we examine DEWA's operational efficiency, investment ‎decisions, and strategic positioning. Our analysis reveals that DEWA achieved exceptional ‎operational performance, recording the world's lowest Customer Minutes Lost at 0.94 minutes ‎in 2024 and maintaining transmission losses at 2% for electricity and 4.5% for water (DEWA, ‎‎2024a). DEWA's financial performance showed consistent growth, with total revenues reaching ‎AED 30.98 billion in 2024, representing a 6.17% increase from the previous year (DEWA, ‎‎2024a). The organization achieved a net profit of AED 7.23 billion and EBITDA of AED 15.7 ‎billion in 2024 (DEWA, 2024a). This research contributes to accounting and economics ‎literature by providing quantitative evidence of operational excellence in utility management ‎and its correlation with financial performance, offering policy-relevant insights for GCC energy ‎sector development and sustainable utility operations‎.
Keywords: Energy Economics; Utility Financial Performance; Operational Efficiency; GCC Energy Sector; ‎Renewable Energy Investment; Strategic Financial Analysis.